Proscribing the Nordic Resistance Movement in Finland: Analyzing the Process and its Outcome - Tommi Kotonen (Journal for Deradicalization, 2021)
The Nordic Resistance Movement (NRM) was banned in Finland in 2020 after a court process lasting more than two and half years. This article details how effective the ban has been and how the organization has adapted to the ban, both during the process and after the verdict. The NRM has followed strategies similar to previous proscription cases, especially National Action in the UK in 2016, with whom NRM members discussed and shared experiences before the banning process began. Adaptation has meant new organizational forms and the founding of new associations. Before the ban, some commentators argued that it would only radicalize NRM members and that they might move to clandestine actions. Based on court records, police investigation files, and materials gathered from registries for trade and associations, this article covers these and other concerns as well as explores whether the goals set for the ban by the authorities have been realized. Along with perspectives on radicalization and adaptation within and around the NRM, a short analysis of the financial activities of the NRM before and after the ban has also been conducted.